Silver Modified Atraumatic Restorative Technique: A Way Towards "SMART" Pediatric Dentistry During the COVID-19 Pandemic - Divya Natarajan (Tehran University of Medical Sciences, 2022)
As the coronavirus disease-2019 pandemic outbreak continues to be a global public health concern, dentists should seek means to provide oral health care with minimal risk. To meet the recommendations of the Center for Disease Control, alternative non-aerosol generating techniques have been proposed to minimize the risk of disease transmission to patients and dental healthcare personnel. Among recent materials, silver diammine fluoride (SDF) has been shown to be effective in preventing and arresting caries. This along with an atraumatic restorative treatment with glass ionomer cements (GICs) makes it a potentially attractive adjunctive therapy for caries management in pediatric patients. In this technique, SDF is applied over carious tissue and the lesion is restored with auto-polymerizing GIC. This review article aims to provide a practical background and clinical guide for the application of silver-modified atraumatic restorative technique (SMART) as a safe way to provide dental services to children during the pandemic.